Formation of Extrachromosomal Circular DNA from Long Terminal Repeats of Retrotransposons in Saccharomyces cerevisiae. Issue 2 (1st February 2016) - Møller, Henrik D; Larsen, Camilla E; Parsons, Lance; Hansen, Anders Johannes; Regenberg, Birgitte; Mourier, Tobias
Abstract: Extrachromosomal circular DNA (eccDNA) derived from chromosomal Ty retrotransposons in yeast can be generated in multiple ways. Ty eccDNA can arise from the circularization of extrachromosomal linear DNA during the transpositional life cycle of retrotransposons, or from circularization of genomic Ty DNA. Circularization may happen through nonhomologous end-joining (NHEJ) of long terminal repeats (LTRs) flanking Ty elements, by Ty autointegration, or by LTR–LTR recombination. By performing an in-depth investigation of sequence reads stemming from Ty eccDNAs obtained from populations of Saccharomyces cerevisiae S288c, we find that eccDNAs predominantly correspond to full-length Ty1 elements. Analyses of sequence junctions reveal no signs of NHEJ or autointegration events. We detect recombination junctions that are consistent with yeast Ty eccDNAs being generated through recombination events within the genome. This opens the possibility that retrotransposable elements could move around in the genome without an RNA intermediate directly through DNA circularization.